CHOLINE TRANSPORTER-RELATED 4 (CTR4) Is Involved in Drought and Saline Tolerance in Rice - Yu Shicong; Luo Ruxian; Zheng Shuqin; Ning Jing; Shi Yuanzhu; Guo Daiming; Jia Liangmeng; Wang Sen; Xiao Guizong; Guo Pengwang; Li Yang; Ma Xiaoding (Rice Science)
The tolerance of rice to drought and saline stress is crucial for maintaining yields and promoting widespread cultivation. From an ethyl methanesulfonate (EMS)-mutagenized mutant library, we identified a mutant that is susceptible to osmotic stress, named Osmotic Stress Sensitivity 1 (Oss1). Using MutMap sequencing, we characterized the role of a choline transporter-related family gene, CTR4 (Choline Transporter-Related 4), in rice’s tolerance to drought and salt stress. CTR4 plays a critical role in regulating membrane lipid synthesis. In knockout mutants, the total membrane lipid content, especially unsaturated fatty acids, was significantly reduced. Compared with the wild type, knockout mutants exhibited decreased membrane lipid stability under drought and salt stress, faster water loss, higher relative electrolyte leakage, and lower levels of proline and soluble sugars, leading to impaired tolerance to drought and salt stress. In contrast, the overexpression of CTR4 enhanced seedling tolerance to drought and saline stress. The overexpression lines displayed lower malondialdehyde levels, reduced relative electrolyte leakage, and slower rates of leaf water loss under stress conditions, thereby improving seedling survival rates during stress. Moreover, lipid synthesis gene expression was down-regulated in CTR4 mutants, potentially exacerbating membrane permeability defects and further compromising stress resistance. These findings suggest that CTR4 mediates choline transport and influences cell membrane formation, thereby enhancing rice defenses against drought and salt stress by maintaining lipid homeostasis.